Innovation of Property Right System Under the Sustainable Development of Chinese University Enterprises - Zhongyuan, Liu (International Journal of Management and Education in Human Development, 2022)
Since the implementation of reform and opening up in China, the domestic university-run industry has made great progress. With the help of talents, scientific and technological advantages, and scientific and technological achievements, all colleges and universities set up their enterprises and made remarkable achievements in accelerating the transformation and industrialization of scientific and technological achievements. In the historical leap period of higher education reform and development, how to do a good job in the property rights reform of school-run enterprises, further strengthen and reform the management of school-run industries, and make the school-run industries standardized management and sustainable development has become a new topic.